The protection of water: ten principles (Polis (Santiago), 2018)
¿Is it possible to establish a decalogue about water in the era of globalization and liberalization of all markets and natural resources? The author beleives it is possible and suggests 10 basic principles to maintain the equilibrium of water among human necesitties and nature. Water cannot be simply concieved as an exploitable resource, but as a planet’s patrimony as well as for the next generations. The 10 principles of Barlow, more than a code, represent an invitation to think about sustainability starting out from local perspective.
Keywords: water; principles; decalogue; fundamental wrights